Training on Household Dirty Water Drainage Management - Putri IS. Samad; Retyana Wahrini; Ganggang Canggi Arnanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Farmers in Samangki Village regarding sanitation is still low, which indicates the need for guidance and guidance efforts to improve the quality of the environment and housing in this village. This PKM was carried out in the rainy land farmers' settlement in Samangki Village, with the Samangki Village Head as the PKM partner. The aim of this PKM is to assist Samangki Village farmers in creating healthy household wastewater drainage channels, while also improving the quality of their housing environment and their overall quality of life. This PKM begins by submitting an application for a location permit to the Maros Regency Village Development Service by the Chair of LP2M UNM Makassar. Outreach activities were carried out in NSamangki Village, especially aimed at the target community. The content of the socialization focuses on the importance of constructing healthy household wastewater drains, the tools and materials used in the construction, as well as the construction model that will be applied. The socialization method involves direct visits to PKM locations, lectures, discussions, and question and answer sessions. The results of this PKM include significant achievements, such as: (a) Increasing Farmer Skills through intensive training and mentoring, (b) Reducing the Risk of Disease by implementing healthy sewers, (c) Improving the Quality of Life for farmer households who take part in this program by a cleaner and healthier environment, as well as (d) a real improvement in the quality of life. Thus, this PKM activity has achieved significant positive results.